2001
DOI: 10.1006/mthe.2001.0428
|View full text |Cite
|
Sign up to set email alerts
|

In Utero AAV-Mediated Gene Transfer to Rabbit Pulmonary Epithelium

Abstract: In utero intra-amniotic administration of adeno-associated virus (AAV) for treatment of cystic fibrosis (CF) has the potential to be an efficient way to target the rapidly dividing undifferentiated cells of the fetal pulmonary epithelium, while simultaneously treating other tissues involved in CF (such as the intestines), but has never before been studied. Intra-amniotic administration of 1x10(12) particles of AAV-luciferase vector to 110 fetal rabbits at 24-25 days gestation resulted in transgene expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…5,12,19,24 However, in general, gene transfer after intra-amniotic vector injection has been inefficient and transient because of the relatively late developmental stage at which these experiments have been performed. 5,26,27 In contrast to previous studies, we have recently reported that early IAGT results in efficient transduction of skin stem cell populations 28 and the ectoderm-derived stem cell populations of the eye, 29 including stem cells in the neuroectoderm-derived retina. However, in the course of these studies we observed a broad range of transduction events involving multiple tissues of all three germ layers.…”
Section: Introductionmentioning
confidence: 60%
“…5,12,19,24 However, in general, gene transfer after intra-amniotic vector injection has been inefficient and transient because of the relatively late developmental stage at which these experiments have been performed. 5,26,27 In contrast to previous studies, we have recently reported that early IAGT results in efficient transduction of skin stem cell populations 28 and the ectoderm-derived stem cell populations of the eye, 29 including stem cells in the neuroectoderm-derived retina. However, in the course of these studies we observed a broad range of transduction events involving multiple tissues of all three germ layers.…”
Section: Introductionmentioning
confidence: 60%
“…AAV vectors have achieved long-term transgene expression in non-human primates (up to 24 months) 20 but only short-term expression, up to 24 days, in rabbits 21 following in utero delivery. In adult mice, AAV efficiently transduced respiratory epithelium for up to 9 months, although a steady decline in transgene expression was reported.…”
Section: Introductionmentioning
confidence: 99%
“…According to several reports [17][18][19] and from our own experience [20,21], the pregnant rabbit is a useful and reliable middle-sized animal model to evaluate proof-of-principle strategies based on gene transfer or cell transplantation into the fetus, which allow accurate organ-directed manipulation and delivery. Using fetal instead of adult donor cells for in utero transplantation approaches may also offer some benefit.…”
Section: Introductionmentioning
confidence: 99%